2018
DOI: 10.5606/tftrd.2018.1535
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy of paraffin therapy and home-based exercise programs in the treatment of symptomatic hand osteoarthritis

Abstract: Objectives: This study aims to investigate the effects of a home-based exercise program in combination with paraffin therapy on pain, functional status, grip strength, and quality of life (QoL) and to compare the outcomes of these two treatment modalities. Patients and methods: This prospective, single-blind, randomized-controlled study included a total of 61 patients (8 males, 53 females, mean age 59.22 years; range, 35 to 78 years) who were diagnosed with hand osteoarthritis (HOA) according to the American C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The study duration ended after 6 weeks. Home exercise along with paraffin application was found to be statistically significantly superior for pain reduction and improvements in hand grip strength, finger pinch strength, functional status, and quality of life in the short term (Kasapoğlu Aksoy and Altan 2018 ). A current randomized controlled study compared the efficacy of paraffin and fluidotherapy treatments for HOA patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study duration ended after 6 weeks. Home exercise along with paraffin application was found to be statistically significantly superior for pain reduction and improvements in hand grip strength, finger pinch strength, functional status, and quality of life in the short term (Kasapoğlu Aksoy and Altan 2018 ). A current randomized controlled study compared the efficacy of paraffin and fluidotherapy treatments for HOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperemia resulting from relaxation of arteriolar smooth muscle fibers and vasodilatation of peripheral veins with paraffin application causes increases in tissue fluid transduction, increased lymph flow, and absorption of exudates. These mechanisms were correlated with reduced pain, increased hand grip strength, and improved functionality and quality of life in the short term for HOA patients (Dilek et al 2013 ; Kasapoğlu Aksoy and Altan 2018 ). Additionally, a current study stated that paraffin treatment is used in routine treatment of HOA patients (Karlıbel et al 2021 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Paraffin wax was combined with other types of intervention (hand exercise, home exercise program and education) with significant improvement in functional status and reducing pain [72,73].…”
Section: Paraffin Wax and Balneotherapymentioning
confidence: 99%
“…Previous studies have shown that paraffin therapy reduces pain and increases joint range of motion in patients with joint spasticity or stiffness. After receiving combined paraffin and ultrasound treatments, improvements in the symptoms of patients with spasticity have been observed (31,32).…”
mentioning
confidence: 99%